PENAPISAN AKTINOMISETES YANG BERSIFAT ANTAGONIS TERHADAP PENYAKIT LAYU BAKTERI TANAMAN CABE - Winarni, Inggit; K, Elizabeth Novi (LPPM Universitas Terbuka, 2007)
Ralstonia solanacearum can cause droop bacteria desease in chilli plants which resulted in productivity’s decreasing. Chemical subtances commonly used to eliminate the bacteria is costly and have negative effect on environment. This research aims to eliminate the varied actinomisetes and to get antagonistics actinomisetes towards the droop bacteria desease of chilli plants. The Botanical forest in Baturaden was chosen because has unique and high diversity microorganism that has characteristic antagonism that pressure growth of other antagonistic’s because of antimicrobe. A number of 18 actinomisetes isolat were successfully isolated and then rejuvenated based on morphology, colours, and shape of the colonies. A characterization of morphology trait towards target bacteria had also been conducted. Six of the 18 actinomisetes isolat have antagonist characteristics towards target bacteria’s growth. Isolat Btrd II.g and Btrd IV.l have the highest resistor activity as indicated by a 6 and 5 mm crystal clear zone. It indicated that actinomisetes isolat Btrd II.g and Btrd IV.l have relatively high antagonist characteristics. Btrd II.g and Btrd IV.l are potential to be used as an environmental friendly way to eliminate droop bacteria desease in chilli plants.